Constructions of solitary wave solutions for huge family of NPDEs with three applications - Hanan A. Alkhidhr; Y. Omar (PLoS ONE, 2025)
This study offers closed-form solutions for the frequently utilised families of nonlinear partial differential equations (NPDEs). This form based on the He’s semi-inverse technique. This form can be considered as a box solver for physicists, engineers and mathematicians. This closed form has several advantages, including eliminating complicated calculations and clearly presenting crucial solutions. Three physical applications are provided in order to validate this closed form technique. The theoretical investigation and given results demonstrate that the suggested technique is efficient and appropriate. For appropriate values of the free parameters, some graphs are used to characterize the dynamical changes of the derived solutions. Finally, our methodology may be extended to various equations emerging in several branches of applied science.